2007
DOI: 10.1177/1077559507300322
|View full text |Cite
|
Sign up to set email alerts
|

Parental Substance Use Disorders and Child Maltreatment: Overlap, Gaps, and Opportunities

Abstract: There are relatively few empirically sound studies or nationally representative data on the number of children in Child Welfare Services (CWS) who are affected by their parents' substance abuse or dependence. The two systems that could systematically monitor this population, CWS and substance abuse treatment, are not required to capture the data elements that would identify families in both systems. The studies that are based on CWS populations or parents in treatment indicate that there is a substantial overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 13 publications
3
98
0
1
Order By: Relevance
“…Parental substance abuse has been identified as a primary contributor to child maltreatment (Dong et al, 2004) and has been indicated or suspected in more than two-thirds of all substantiated cases (Jones, 2005). Children of parents who abuse substances are much more likely to be placed in foster care (U. S. Department of Health and Human Services, 1999;Young, Boles, & Otero, 2007) and are in out-of-home placements longer than youth removed for other reasons (Vanderploeg et al, 2007). Moreover, substance abuse often co-occurs with IPV, and has been documented in both victims (El-Bassel, Gilbert, Wu, Go, & Hill, 2005) and perpetrators (Fals-Stewart, Golden, & Schumacher, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Parental substance abuse has been identified as a primary contributor to child maltreatment (Dong et al, 2004) and has been indicated or suspected in more than two-thirds of all substantiated cases (Jones, 2005). Children of parents who abuse substances are much more likely to be placed in foster care (U. S. Department of Health and Human Services, 1999;Young, Boles, & Otero, 2007) and are in out-of-home placements longer than youth removed for other reasons (Vanderploeg et al, 2007). Moreover, substance abuse often co-occurs with IPV, and has been documented in both victims (El-Bassel, Gilbert, Wu, Go, & Hill, 2005) and perpetrators (Fals-Stewart, Golden, & Schumacher, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Research also indicates links between parental substance abuse and child maltreatment (see Young, Boles, & Otero, 2007). An estimate by the National Committee for Prevention of Child Abuse suggests that one in 13.3 children living with a substance-abusing parent experiences severe maltreatment each year (as cited in Besinger, Garland, Litrownik, & Landsverk, 1999).…”
Section: Parental and Familial Contextmentioning
confidence: 99%
“…Les programmes destinés aux femmes enceintes qui ont une consommation problématique de substances sont plus présents qu'avant, mais leur nombre est loin de suffire aux besoins 15 . La plupart des programmes sont encore destinés à une clientèle hétérogène et ne tiennent pas compte des besoins multiples et complexes de ces femmes, comme ceux reliés à la pauvreté et au soutien en matière de parentalité et de développement des enfants 16,17 .…”
unclassified